Pengaruh Lingkungan Kerja dan Kesempatan Pengembangan Karir Terhadap Kinerja Karyawan PT.BFI FINANCE Semarang - Santhiko, Anggoro; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2018)
The existence and success of an organization in achieving its goals, can not be separated from the human resources factor. human resources have an important role in various sectors, because human resources is a key factor driving all factors in the company. The importance of the role of human resources makes the organization should seek to maximize the existing human resources in the organization, and one way is to improve the performance of human resources in the organization optimally. The purpose of this study to determine the effect of work environment, and career development opportunities on employee performance. The type of research is explanatory research, data collection techniques are questionnaires and interviews. The sample in the study amounted to 72 respondents with sampling technique is the sampling census / population. Scale measurement using Likert Scale. Data analysis in this study, using quantitative analysis. Quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple regression analysis, determination coefficient, significance test, (t test and F test) and path analysis that using SPSS tools. Based on the results of this study shows that the work environment (ð‘‹1) and career development opportunities (ð‘‹2) both simultaneously and partially affect employee performance (ð‘Œ ) Pursuant to result of path analysis, direct influence of work environment and career development opportunity have an effect on to employee performance. Based on these results, the authors suggest that the company can provide a conducive working environment and adequate equipment to accomplish tasks assigned by employees. In addition it also provides ongoing skills and talent training for employees to keep growing, and provide clear knowledge on employees about existing career development paths in the company.